Chronic urticaria in Chinese population: a hospital‐based multicenter epidemiological study. Issue 3 (20th December 2013) - Zhong, H.; Song, Z.; Chen, W.; Li, H.; He, L.; Gao, T.; Fang, H.; Guo, Z.; Xv, J.; Yu, B.; Gao, X.; Xie, H.; et al.
Abstract Background The epidemiologic profiles of chronic urticaria (CU) vary considerably among regions, and few such data are available from China. Methods We performed a multicenter open questionnaire investigation about the clinical and laboratory features of CU, defined as recurrent wheals with/without angioedema lasting for ≥6 weeks, among 3027 patients. Results Female preponderance was observed (female/male ratio, 1.46 : 1). The mean age at diagnosis was 34.7 ± 13.8 years, and the mean disease duration was 18.5 ± 46.1 months (range, 1.5–127 months). Patients were classified as having chronic spontaneous urticaria (CSU, 61.0% of patients), physical urticaria (PU, 26.2%), or other urticaria types (OU, 2.3%). Nocturnal attacks were reported by 60% of cases. The Urticaria Activity Score (UAS) in patients with CSU was 3.8 ± 1.4. The mean Dermatology Life Quality Index was 7.3 ± 3.4 (range 0–30). Induction or exacerbation of wheals with alcohol drinking was reported by 55.7% of patients. Chronic hepatitis B was less prevalent in our CU patients compared with the general Chinese population (2.7% vs 7%). Positive autologous serum skin tests (ASSTs) were observed in 66.9% of patients. Patients with positive ASST had higher UAS, greater angioedema frequencies, longer disease durations, and poorer QoL compared with patients with negative ASST (P < 0.05). Conclusion In this Chinese population, CU usually affected youth, and CSU was the most common subtype. Autoreactivity and alcohol consumption were the top two triggers for CU, whereas latent infectious and chronic inflammatory diseases were not as common as in previous reports.